Adherence and Predictors of Endocrine Therapy Use Among Breast Cancer Patients in a Private Hospital: A Cross-Sectional Study - Setiawardani, Maria Fitri; Cholisoh, Zakky; Hapsari, Pramudita Mila (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2026)
Background: Breast cancer has a high incidence rate. One of the treatments involves long-term endocrine therapy, which can cause boredom in patients with cancer, leading to non-compliance with therapy. Objective: This study aimed to evaluate adherence and identify the variables that affect the level of adherence in patients with breast cancer receiving endocrine adjuvant therapy at a private hospital in Central Java. Methods: This cross-sectional study used purposive sampling. Data were collected from 87 respondents in total. Data were collected using questionnaires and patient medical records. Results: We categorised the patient adherence level as adherent (65.5 %) and non-adherent (34.5 %). The logistic regression test revealed a relationship between adherence and education level (p-value=0.001; OR=0.056; 95% CI 0.012-0.281), stage (p-value=0,002; OR 0.096; 95% CI 0.022-0.424), and other medication use (p-value=0,020; OR=0.061; 95% CI 0.006-0.650). This indicates that education level, cancer stage, and other medication use significantly influenced the adherence rate of patients receiving endocrine adjuvant therapy. These findings emphasise the need for targeted educational support and optimised medication management to improve adherence among patients undergoing long-term endocrine therapy.